Production of polymer filament-shaped piezoelectric sensors for e-textiles applications - Carvalho, Helder (2012)
This work aims at the development of piezoelectric materials for flexible sensors produced with various geometries, at low cost and high production rates, adequate for the industrial scale. In particular the filament form, appropriate for integration into textiles, is described, but other geometries, such as tape, are also being studied. The filaments are produced by co-extrusion of multiple layers with piezoelectric and electrically conductive polymer composites.